MEMBANGUN BUDAYA ORGANISASI UNGGUL SEBAGAI UPAYA MENINGKATKAN KINERJA KARYAWAN DI ERA KOMPETITIF - Hakim, Lukman (Benefit: Jurnal Manajemen dan Bisnis, 2011)
One of the variable related to the improvement of business or organizational performance determination is organizational culture. Organizational culture is value and belief system that adopted together inspired by belief and a common interaction with people of a company, the structure of the organization and supervision systems to produce behavioral norms. Cultural organizations have some of the functions within an organization, among other, have a role in determining boundaries, which creates a difference between one organization to another. Organizational culture also serves to convey a sense of identity to members of the organization, facilitate the continuation of commitment to reach a wider range, helping to bind the organization together by providing appropriate standards of what should be said and done the employee, former employee performance improvement. Characteristic of organizational culture, among others: learn, share, trans-generation, influence perception, adaptation. Characteristics of the Islamic culture, among others: work is a "worship", work-benefit principle beneficiaries, is the actualization of the ability of his wits to work, work with âtawazunâ (harmony), observing the principle of âhalalâ.